The Implementation of An Adapted International Baccalaureate (IB) Curriculum To Improve Students English Learning Outcomes In Rural School: An Indonesian TESOL Context - Aip Syaepul Uyun (Gunung Djati Conference Series, 2026)
This study investigates the implementation of an adapted International Baccalaureate (IB) curriculum to improve students’ English learning outcomes in a rural Indonesian TESOL context. The research was conducted as a continuation of a Research and Development (R&D) study, focusing on the implementation and evaluation phase of a previously designed curriculum. The study involved expert validation and field testing with students in a rural partner school. Data were collected through questionnaires, interviews, and classroom observations, and analyzed using descriptive quantitative and qualitative approaches. The findings reveal that the adapted IB curriculum was effectively implemented, with positive responses across four key indicators: understanding, engagement, skill development, and contextual relevance. Students demonstrated a high level of comprehension (85%), supported by systematic and scaffolded material organization. Engagement was also notably high (88%), indicating the effectiveness of student-centered and interactive learning approaches. In terms of skill development, 82% of students reported improvements in their English abilities, particularly in basic communication skills, although productive skills such as speaking and writing still require further enhancement. The highest result was found in contextual relevance (88%), showing that learning materials closely aligned with students’ daily lives significantly improved motivation and comprehension. The study concludes that integrating IB principles particularly Content and Language have beneficial impacts into the success of instruction.